1993
DOI: 10.1088/0022-3727/26/8b/017
|View full text |Cite
|
Sign up to set email alerts
|

A dialysis technique for determining aggregate concentrations in crystallizing protein solutions

Abstract: The authors have adapted a dialysis technique which provides aggregate concentrations of protein molecules in solutions which lead to crystal growth. In dialysis, the flux across a semipermeable membrane is directly proportional to the concentration of the diffusible solute inside the bag provided that the solute concentration in the bulk solution is infinitely dilute. Using membranes of varying porosity, the concentrations of different size solutes can be measured by measuring the flux rate across the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Currently in the field of protein crystal growth there is experimental evidence both supporting and disputing the presence of structured aggregates in crystalline solutions. For lysozyme, evidence supporting the aggregation theory comes from dialysis kinetics (Wilson, Adcock & Pusey, 1993), neutron scattering (Boue, Lefaucheux, Robert & Rosenman, 1993), sedimentation equilibrium (Sophianopoulos & Van Holde, 1961, 1964, nuclear magnetic resonance (Shindo, Cohen & Rupley, 1977), light scattering intensity (Pusey, 1991) and calorimetry (Banerjee, Pogolotti & Rupley, 1975). Some of these studies were carried out prior to 1980 when the conditions used for studying lysozyme aggregation were close to physiological ionic strength and neutral pH.…”
Section: Introductionmentioning
confidence: 99%
“…Currently in the field of protein crystal growth there is experimental evidence both supporting and disputing the presence of structured aggregates in crystalline solutions. For lysozyme, evidence supporting the aggregation theory comes from dialysis kinetics (Wilson, Adcock & Pusey, 1993), neutron scattering (Boue, Lefaucheux, Robert & Rosenman, 1993), sedimentation equilibrium (Sophianopoulos & Van Holde, 1961, 1964, nuclear magnetic resonance (Shindo, Cohen & Rupley, 1977), light scattering intensity (Pusey, 1991) and calorimetry (Banerjee, Pogolotti & Rupley, 1975). Some of these studies were carried out prior to 1980 when the conditions used for studying lysozyme aggregation were close to physiological ionic strength and neutral pH.…”
Section: Introductionmentioning
confidence: 99%
“…It remains an open question whether lysozyme forms large aggregates when undersaturated or when in the prenucleation phase of crystallization. Recent data that support aggregation are from small-angle neutron scattering (SANS) experiments (Niimura et al, 1995;Boue et al, 1993) and dialysis kinetics (Wang et al, 1996;Wilson et al, 1993Wilson et al, , 1996. In contrast, some dynamic light-scattering (DLS) studies have concluded that scattering data that may suggest, at first examination, the formation of aggregates, are more accurately explained in terms of interparticle interactions (Muschol and Rosenberger, 1996;Eberstein et al, 1994).…”
mentioning
confidence: 99%
“…Evidence of oligomers in supersaturated lysozyme solutions comes from many sources including sedimentation equilibrium (Sophianopoulos & Van Holde, 1961, 1964, calorimetry (Banerjee et al, 1975), nuclear magnetic resonance (Shindo et al, 1977), light-scattering intensity (Pusey, 1991), dialysis kinetics (Wilson et al, 1993) and neutron scattering (Boue et al, 1993). Some of these studies were performed prior to 1980 when the conditions used for studying lysozyme aggregation were close to physiological ionic strength and neutral pH.…”
Section: Introductionmentioning
confidence: 99%